Pengaruh Estimasi Permintaan Bahan Bakar Pertalite Pada PT Pertamina (Persero) Periode 2020–2024 - Zainal Ruma (Jurnal Ilmu Manajemen, Bisnis dan Ekonomi, 2025)
This study aims to analyze the influence of economic factors on the estimated demand for Pertalite fuel at PT Pertamina (Persero) during the 2020–2024 period. The background of this research is based on the increasing consumption of Pertalite in Indonesia in line with fluctuations in fuel prices, economic growth, and population growth. The originality of this research lies in the development of an empirical model to estimate the demand for Pertalite using macroeconomic variables, including Pertalite prices, public income (GDP per capita), population, and substitute fuel prices. This study uses a quantitative approach with descriptive and verifiable methods, where data is analyzed using multiple linear regression with the help of SPSS software. The classical assumption test showed that the model met the criteria of normality and was free of multicollinearity, heteroscedasticity, and autocorrelation, making it worthy of analysis. The regression results showed that the price of Pertalite had a significant negative effect on estimated demand, GDP per capita and population had a significant positive effect, while the price of substituted fuel had a positive but insignificant effect. A determination coefficient (R²) of 0.847 indicates that the model explains most of the variation in Pertalite demand estimates. These findings confirm that demand for Pertalite in Indonesia is inelastic because it remains high despite price fluctuations. The results of this study are expected to be the basis for the government and PT Pertamina (Persero) in formulating a strategy for pricing, subsidies, and energy distribution that is more adaptive to national economic dynamics.